STRATEGI PENGEMBANGAN DESA WISATA CAU BELAYU SEBAGAI DESA WISATA YANG BERDAYA KOMPETITIF: STRATEGI PENGEMBANGAN DESA WISATA CAU BELAYU SEBAGAI DESA WISATA YANG BERDAYA KOMPETITIF - Wayan Wikananda Yudha; Ni Made Tirtawati; Ida Bagus Gede Agung Widana (Journal of Applied Science in Tourism Destination, 2025)
Cau Belayu Tourism Village is one of the tourist villages located between the border of Tabanan regency and Badung regency, after the establishment of the Regent Decree, Cau Belayu Tourism Village still has not shown significant development. Cau Belayu Tourism Village in Tabanan Regency is experiencing obstacles in its development. Cau BelayuTourism Village faces difficulties in managing human resources who serve as managers, in addition, the management of tourist destinations is also one of the obstacles faced Another obstacle is the problem of marketing. Cau Belayu Tourism Village may be less effective in promoting its attractions to potential tourists. In addition, the lack of variety of tourism products is also an obstacle. Cau Belayu Tourism Village needs to develop more varied and attractive tourism products. Therefore, in this study, researchers want to know more deeply the strengths, weaknesses, opportunities and threats of the Cau BelayuTourism Village to analyze its development strategy. The approach is descriptive qualitative, and the sources are identified using the pentahelix method based on the following criteria: the sources must be at least 17 years old, have a thorough understanding of the tourist village of Cau Belayu, and be able to communicate effectively through observation, interviewing, and documentation of the research instruments (SWOT, IFAS, and EFAS). The SO Strategy (Strength-Opportunities) score IFAS 0.14 and EFAS 0.42 obtained from the study's results indicate that an aggressive strategy will be used to develop the Cau Belayu tourist village as a suitable competitive tourist village. This strategy will include partnerships for integrated tourism packages, collaboration with government programs, technology innovation for attractions, strengthening branding through cooperation, and global trend-based promotion.